2000
DOI: 10.1055/s-2000-10990
|View full text |Cite
|
Sign up to set email alerts
|

Effet de l’adaptation à l’obscurité sur le flux rétinien1

Abstract: These results do not support the hypothesis that Fret in normal volunteers is increased during DA. Rather, they strongly suggest that the transient increase in flux observed after DA is induced by the transition from dark to light (FNSRS #3200-043157 et CNR, It. #95.01715.CT04).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…One would not then expect a change in retinal blood flow between darkness and steady light, which was supported by results with an infrared laser Doppler method in humans. Riva et al (Riva et al, 2000) found a transient increase in retinal blood flow at the onset of light, but no maintained change, and suggested that previous measurements (Feke et al, 1983; Riva et al, 1983) that found a dark-light difference were probably influenced by this transition. However, nearly simultaneously with the more recent study by Riva et al, Havelius et al (Havelius et al, 1999), using an ultrasound (color Doppler) method in humans, reported a modest increase in central retinal artery velocity of about 20% during 25 min of darkness relative to steady light (120 to 1350 lux).…”
Section: Fundamentals Of O2 Supply To the Retinamentioning
confidence: 87%
See 1 more Smart Citation
“…One would not then expect a change in retinal blood flow between darkness and steady light, which was supported by results with an infrared laser Doppler method in humans. Riva et al (Riva et al, 2000) found a transient increase in retinal blood flow at the onset of light, but no maintained change, and suggested that previous measurements (Feke et al, 1983; Riva et al, 1983) that found a dark-light difference were probably influenced by this transition. However, nearly simultaneously with the more recent study by Riva et al, Havelius et al (Havelius et al, 1999), using an ultrasound (color Doppler) method in humans, reported a modest increase in central retinal artery velocity of about 20% during 25 min of darkness relative to steady light (120 to 1350 lux).…”
Section: Fundamentals Of O2 Supply To the Retinamentioning
confidence: 87%
“…Under steady state conditions, previous studies have shown no major difference in metabolism in the inner retina between light- and dark-adapted eyes, although as discussed in section 3.2.1, there may be a small change in blood flow (Braun et al, 1995; Riva et al, 2000). To induce substantial retinal hemodynamic alterations, however, strong flickering light for at least 30 seconds is employed (Mishra et al, 2011).…”
Section: Approaches To Retinal Oxygenmentioning
confidence: 92%
“…However, this unavoidable transition from dark-to-light conditions during fundus photography seems in itself to cause rapid changes in the retinal blood flow. 11,14 A major advantage of our examination technique is that the fundus imaging was made using near-infrared light, eliminating the effects of rapid dark-light changes that occur during normal photography. Further, the analysis of the recordings made with the RVA allowed us to achieve accurate results by averaging the periodic changes of vessel diameter (e.g., pulse waves) using 1500 to 2000 measurements made over a period of 3 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they could not actually measure in darkness, only before and after dark adaptation. Later, Riva et al 11,14 adapted their method and used near-infrared laser Doppler flowmetry to measure the flow velocities in retinal branch vessels during dark adaptation. Using this new method they did not find significantly increased flow velocity in the dark-adapted retinal vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Light exposure following dark adaptation seems to induce a rapid transient increase in the retinal blood flow velocity, reaching peak value at 30–60 seconds (Riva et al. 2000 ). The study of Feke et al.…”
Section: Discussionmentioning
confidence: 99%